Gambaran Kualitas Hidup Penderita Kusta di Kabupaten Lembata - Making, Maria Imakulati; Aulawi, Khudazi; Warsini, Sri (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file